2022
DOI: 10.1111/acel.13759
|View full text |Cite
|
Sign up to set email alerts
|

Cellular expansion of MSCs: Shifting the regenerative potential

Abstract: Mesenchymal‐derived stromal or progenitor cells, commonly called “MSCs,” have attracted significant clinical interest for their remarkable abilities to promote tissue regeneration and reduce inflammation. Recent studies have shown that MSCs' therapeutic effects, originally attributed to the cells' direct differentiation capacity into the tissue of interest, are largely driven by the biomolecules the cells secrete, including cytokines, chemokines, growth factors, and extracellular vesicles containing miRNA. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 159 publications
0
15
0
Order By: Relevance
“…Senescent MSCs, therefore, have reduced therapeutic potential and may even be harmful if transplanted into patients. We have also observed that during the expansion of MSCs isolated from adipose tissue and bone marrow, accumulation of senescent cells occurs [228].…”
Section: Mscs and Senolytics: Combinatory Therapeutic Paradigmsmentioning
confidence: 72%
“…Senescent MSCs, therefore, have reduced therapeutic potential and may even be harmful if transplanted into patients. We have also observed that during the expansion of MSCs isolated from adipose tissue and bone marrow, accumulation of senescent cells occurs [228].…”
Section: Mscs and Senolytics: Combinatory Therapeutic Paradigmsmentioning
confidence: 72%
“…They also cause MHC class II + macrophage differentiation with increased l‐arginase activity and secretion of IL‐10 in the tumor microenvironment (Biswas et al 2019). It is important to note that despite the high durable response rates to immunotherapies, a large percentage of patients do not respond due to primary, adaptive, or acquired resistance to immune therapies (Miclau et al 2023). In the tumor immunological microenvironment, MSC‐Exos can play a contrasting dual immunomodulatory role by altering the activities of various immune cell types, including NK cells, M‐MDSCs, and B‐ and T‐lymphocytes (Biswas et al 2019; Zhou et al 2021).…”
Section: Msc‐exos and Immune Modulation In Cancermentioning
confidence: 99%
“…The term “secretome” describes the group of molecules that cells secrete, comprising lipids, proteins, nucleic acids, and other bioactive compounds (Daneshmandi et al 2020). The diversity found in the secretome of EVs showcases the distinctive roles and conditions exhibited by the donor cells (Miclau et al 2023). The diverse biomolecules carried by EVs also reflect the functional diversity of these vesicles (Driscoll and Patel 2019; Walker et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Large bone defects are often associated with non- or delayed-union disease, which is primarily ascribed to the inadequate quantity of MSCs and the limited osteoinductive ability of the resident MSCs in the lesional milieu. Therefore, tissue engineering strategies involving the delivery of ex vivo MSCs with an osteoinductive ability from carriers have been developed to promote bone development and repair. , Nevertheless, the manipulation of exogenous MSCs for clinical application still faces formidable challenges due to their inadequate in vitro expansion, which shifts the regenerative potential in long cultures, as well as their high cost, safety concerns, and limited in vivo survival rates at damaged sites. …”
Section: Introductionmentioning
confidence: 99%